Abundance: the archaeology of plenitude - Smith, Monica L., editor; University Press of Colorado, publisher (Colorado State University. Libraries, 2017)
Using case studies from around the globe and multiple time periods, Smith makes the case that abundance provides an essential explanatory perspective on ancient peoples' choices and activities. Focusing on plenitude enables the understanding of cohesive behaviors that were equally important for the development of social complexity.--Provided by publisher.
The archaeology of abundance / Monica L. Smith -- Rethinking the impact of abundance on the rhythm of bison hunter societies / María Nieves Zedeño -- Abundance in the archaic: a dwelling perspective / Christopher R. Moore and Christopher W. Schmidt -- Water, wind, breath: seeking abundance in the northern American Southwest / Mark D. Varien, James M. Potter, and Tito E. Naranjo -- Abundance in the ancient Maya village of Ceren / Payson Sheets -- Savanna products and resource abundance: asking the right questions about ancient Maya trade and urbanism / Traci Ardren -- Abundant exotics and cavalier crafting: obsidian use and emerging complexity in the northern Lake Titicaca Basin / Elizabeth Klarich, Abigail Levine, and Carol Schultze -- Coping with abundance: the challenges of a good thing / Katheryn C. Twiss and Amy Bogaard -- Pottery: abundance, agency, and choice / Justin St. P. Walsh -- "Excessive economies" and the logics of abundance: genealogies of wealth, labor, and social power in pre-colonial Senegal / François G. Richard -- Production, distribution, and aesthetics: abundance and Chinese porcelain from Jingdezhen, 1350-1800 A.D. / Stacey Pierson.
Keywords: Social archaeology -- Case studies; Material culture -- Case studies; Consumption (Economics) -- Social aspects -- History -- Case studies; Economic anthropology -- Case studies